IMF Staff papers : Volume 14 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1967)
This paper presents a study to review fluctuations in Japan's balance of payments and the role of short-term capital flows. Based on annual data, it appears that Japan has passed through two additional cycles after the 1952-55 and 1955-58 cycles covered by Narvekar's studies. In general, the annual data show clearly that the flows of short-term capital have tended to fluctuate in a direction opposite to that of the fluctuations in the basic balance of payments. Thus, the short-term capital inflow increased substantially as the basic surplus fell sharply from 1959 to 1960 and increased further still as the basic balance went into heavy deficit in 1961. Short-term capital flows helped to moderate the fluctuations in Japan's over-all balance of payments, compared with the fluctuations in its basic balance, and thus played an anticyclical role in Japan's balance of payments during 1959-1966. During 1965, the basic balance showed a small deficit in the first quarter, a small surplus in the second quarter, and large surpluses in the third and fourth quarters. This review of monetary policy changes indicates an intimate relationship between changes in Japanese monetary policy and fluctuations in Japan's basic balance of payments during 1959-1966.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet